Late-glacial fluctuations of two southern Patagonia outlet glaciers revealed by high-resolution seismic surveys. Issue 1 (September 2020) - Lodolo, Emanuele; Lozano, Jorge; Donda, Federica; Bran, Donald; Baradello, Luca; Tassone, Alejandro; Romeo, Roberto; Paterlini, Marcelo; Grossi, Maurizio; Caffau, Mauro; Vilas, Juan Francisco
Abstract: Lago Argentino hosts various calving glaciers, among them the famous Perito Moreno. Whereas the onland late Pleistocene–Holocene glacial history is rather well constrained, the submerged glacier-related features were until now undisclosed. Here we present a series of high-resolution seismic profiles revealing moraine bodies associated with the late-glacial glacier dynamics and the first bathymetric map of the Brazo Rico and Brazo Sur, the two southern arms of Lago Argentino. At the eastern termination of Brazo Rico, we identified at the lake floor the submerged expression of the Puerto Bandera 3 moraine mapped onshore, which represents the oldest event (12, 660 ± 70 cal yr BP oldest minimum age) recognized in this lake arm, and seven other younger events expressed by a series of terminal and recessional moraines. Along the Brazo Sur, few moraine bodies have been imaged by seismic data. Here, the youngest temporal constraint comes from the Frías moraine (ca. 6000 cal yr BP), which closes off the southern end of the Brazo Sur. At the confluence of the two arms, the Perito Moreno and the former Frías glacier merged and flowed toward east during their late-glacial maximum advance (i.e., Puerto Bandera 1 moraine). The subaqueous evidence of moraine bodies testifies to the occurrence of previously undocumented pulses of the Perito Moreno and former Frías glaciers within the general phase of late Pleistocene–Holocene regression.